Epithelial-mesenchymal transition and stem cells in colorectal cancer progression - M. A. Shyshkin; T. O. Khrystenko (Journal of Education, Health and Sport, 2020)
Introduction. Colorectal cancer (CRC) is the third leading cause of cancer-related death worldwide. Studying invasion and metastasizing mechanisms in colorectal carcinogenesis is gaining momentum. The purpose of the study was to analyze immunohistochemical (IHC) expression levels of epithelial and mesenchymal phenotypic markers, as well as cancer stem cells markers on I-IV (pTNM) stages of CRC. Materials and methods. Histopathological and IHC studies of 53 CRC were conducted. IHC study was carried out using antibodies against E-cadherin, CK-20, α-SMA, vimentin, CD44, and ALDH1. Results. CRC is characterized by low E-cadherin expression level that decreases during the I-IV stages sequence and by medium CK-20 expression level that decreases during the studied sequence. Furthermore, CRC is characterized by medium α-SMA and vimentin expression levels that increase during the studied sequence. These findings indicate parallel epithelial phenotype losing and mesenchymal phenotype acquiring by the cancer cells that happen during colorectal adenocarcinoma progression from the I to the IV stages. CD44 expression by the tumor stromal cells was described in this study. The median of CD44+ cells area equal to 61,26 (42,58; 79,15) % of CRC stromal cells. This index significantly increases from the I to the III stages of the tumor. ALDH1 expression by both cancer cells and stromal cells was described as well. The median of ALDH1+ stromal cells area equal to 40,22 (22,54; 47,77) %, the median of ALDH1+ cancer cells area equal to 42,15 (32,06; 50,42) %. The index of ALDH1+ stromal cells area significantly increases from the I to the III stages of the tumor whereas the index of ALDH1+ cancer cells area significantly increases from the III to the IV stages of the tumor. Moreover, correlations between the studied markers expression were revealed that proves the connection between epithelial-mesenchymal transition and stemness acquisition in CRC progression.